2009
DOI: 10.1080/13557850802056448
|View full text |Cite
|
Sign up to set email alerts
|

Changing the conversation about prostate cancer among African Americans: results of formative research

Abstract: The findings suggest that most potent interventions may combine survivor-led education with mass media and institution-based outreach. Such comprehensive programs could shift social norms that inhibit conversation and foster fear, leading in turn to more informed decisions and better treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…Prior research has shown that community organizations routinely ignore the IDM requirement (Wray et al, 2009). This project sought to strike a balance between the requirements of the prescribed IDM model and PCa screening guidelines and the realities in which communitybased organizations work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has shown that community organizations routinely ignore the IDM requirement (Wray et al, 2009). This project sought to strike a balance between the requirements of the prescribed IDM model and PCa screening guidelines and the realities in which communitybased organizations work.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al, 2008). Prior research in St. Louis has identified that many African American men are underserved with limited access to health care and educational outreach programs (Wray et al, 2009). Recent research has encountered a nearly fivefold risk of late-stage diagnosis for underserved men compared with national data (19% compared with 4%).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Patients often need to quickly build new relationships with oncologic care providers while managing the overwhelming demands of information, treatment decision-making, 10 psychological distress, and financial stress. 11,12 A pattern of ineffective patient-provider communication can lead to lack of understanding of prostate cancer and treatment options, 13 which may prevent men from making informed decisions, from receiving optimal treatments, and from achieving positive health outcomes, 14 and may lead to more decisional regrets. 9 …”
Section: Introductionmentioning
confidence: 99%
“…The other half of the relationship, the interaction with provider, is also important, in that access to a provider was a key variable in predicting prostate cancer screening, independent of demographic variables. 11 The provider has an important role in screening decisions; provider communication style, provider encouragement and provider sharing information with the patient all were significantly and positively related to screening. 10 Providers often have knowledge and attitudes that influence their abilities to assist patients in medical decisions.…”
Section: Introductionmentioning
confidence: 99%
“…10 For example, prostate check up and symptom knowledge was low in both African American and Caucasian men. 11 Beliefs varying by culture and ethnicity of surveyed men were important in how they approached prostate cancer screening and treatment. 12 These data indicate that men without information and ways to make sense of that information are at risk for being unable to make an informed decision about whether to get screened for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%